UJI EFEKTIVITAS FORMULASI SEDIAAN KRIM EKSTRAK KULIT BUAH PISANG GOROHO (Musa acuminafe L.) TERHADAP BAKTERI Staphylococcus aureus (PHARMACON, 2020)
ABSTRACTÂ Goroho Banana Skin (Musa acuminafe L.) is a plant that contains flavonoid compounds, saponins and tannins that can inhibit bacterial growth. This study aims to test the antibacterial effectiveness of ethanol extract cream of goroho banana peel and evaluate the preparations using parameters of physical properties and physical stability. This research uses laboratory experimental methods. Cream formula is made with a variety of ethanol extract concentrations of Goroho Banana peel 2.5%, 5%, 7.5%, 10%, 12.5%. Goroho Banana peel extract was obtained by maceration using 96% ethanol solvent. The study of antibacterial test of ethanol extract of Goroho Banana peel using wells method on Staphylococcus aureus bacteria resulted in inhibition of 7.03 Â± 3.29 mm at a concentration of 12.5%. All tests are carried out before and during the cycling test. The results obtained before and during the cycling testshowed that the cream preparations met organoleptic requirements, homogeneity, cream pH 6.807 (4.5-6.5), cream adhesion 9.63 seconds (